Discovery of novel ketoxime ether derivatives with potent FXR agonistic activity, oral effectiveness and high liver/blood ratio. (1st August 2021) - Tang, Xuehang; Ning, Mengmeng; Ye, Yangliang; Gu, Yipei; Yan, Hongyi; Leng, Ying; Shen, Jianhua
Graphical abstract: Highlights: A series of novel ketoxime ether derivatives were designed and synthesized. 13j and 13z were evaluated both in vivo and in vitro. 13j and 13z showed potent agonistic activity in FXR activation assay. 13j and 13z displayed high liver/blood ratios. 13j and 13z exhibited low agonistic effects to hTGR5. Abstract: The farnesoid X receptor (FXR) is a promising therapeutic target for nonalcoholic steatohepatitis (NASH) and other bile acid related diseases because it plays a critical role in fibrosis, inflammation and bile acid homeostasis. Obeticholic acid (OCA), a FXR agonist which was synthesized from chenodeoxycholic acid, showed desirable curative effects in clinical trials. However, the pruritus which was the main side effect of OCA limited its further applications in NASH. Although pruritus was also observed in the clinical trials of non-steroidal FXR agonists, the proportion of patients with pruritus was much smaller than that of OCA. Thus, we decided to develop non-steroidal FXR agonists and discovered a series of novel FXR agonists which were synthesized from GW4064 by replacing the stilbene group with ketoxime ether. Encouragingly, in the following biological tests, our target compounds 13j and 13z not only showed potent FXR agonistic activities in vitro, but also effectively promoted the expression of target genes in vivo. More importantly, in the pharmacokinetic experiments, compounds 13j and 13z displayed high liver/blood ratio characteristics which were helpful to reduce the potential side effects which were caused by prolonged systemic activation of FXR. In summary, our compounds were good choices for the development of non-steroidal FXR agonists and were deserved further investigation.